DISTRIBUSI PENDAPATAN PETANI KACANG MERAH DI DESA SENDANGAN KECAMATAN TOMPASO - Annabel M. Warouw; Eyverson Ruauw; Octavianus Porajouw; Jenny Baroleh (COCOS, 2013)
ABSTRACTThe national income distribution reflects the equal or unequal distribution of the development result of the populations in a country. The purpose of this research is to calculate and to compare the basic income distribution with other incomes of the farmers. This research uses the primary data and secondary data with 30 farmers respondens.The result of the research shows that the Gini Coeficient in the research area is 0, 3943 for the basic income and 0, 3008 for the basic income with other incomes. Paying attention to the Gini Coeficient, means that the unequal income or the uneven income in the research area belongs to the moderate and low unequality.Based of Gini Coeficient, distribution income more equal in basic income with other income than just basic income. It means the other income more in the farmers at low income and middle income. Because of that suggested for the farmer specially in low income group to increase their income from other income another their basic income (red been farm).